Desenvolvimento e avaliação de um jogo para auxiliar o ensino de história do design utilizando realidade virtual e interface cérebro-computador - Melo, Lucas Severo (2024)
This master's dissertation addresses the development and evaluation of a high-fidelity prototype of a serious game for teaching Design History at the higher education level, utilizing innovative technologies such as Brain-Computer Interfaces (BCI) and Virtual Reality (VR). BCIs, which use electroencephalography (EEG), have seen significant growth in fields such as healthcare and digital games. This is due to the emerging need to develop effective alternatives for diagnosing and treating a variety of neurological disorders affecting children and adolescents. VR, in turn, adds an extra layer of immersion for the user, enhancing the effectiveness of BCIs. In the educational context, the diversity of activities and the exploration of the environment in the classroom are valuable strategies to complement teaching and ensure effective learning. In this regard, the serious game developed in this work aims to provide an engaging and effective learning experience. The usability evaluation of the serious game was conducted using the CEGE (Core Elements of the Gaming Experience) questionnaire instrument, with the goal of determining its suitability and usefulness for the user. A case study with 18 students was conducted, during which aspects such as the game's usability, student concentration, and other relevant data for game progress were verified, yielding positive results in both usability and the effectiveness of the proposed challenge. This work aims to open a broader field of possibilities for teaching disciplines using Virtual Reality and Brain-Computer Interface technologies in a playful way, providing a more engaging and effective learning experience. This study contributes to the evolution of higher education, particularly in the field of Design, through the integration of innovative technologies and effective pedagogical practices, resulting in the construction of a game and its evaluation outcomes.